Hydrogen Production in the Radiolysis of Dodecane and Hexane. Issue 3 (16th April 2017) - LaVerne, Jay A.; Kleemola, Sarah R.
ABSTRACT: The yields of molecular hydrogen, H2, have been measured in the radiolysis of dodecane and hexane following radiolysis by γ-rays and a variety of heavy ions. Measured yields with γ-rays are found to be slightly higher than literature values and decrease by about 25% on aeration of the sample. Increasing the linear energy transfer (LET) from γ-rays to radiolysis with protons results in a decrease of H2 yields by about 15% due to the increased importance of second-order H atom combination reactions. A further increase in LET results in a slight increase in H2 yields.